The determinants of agglomeration economies in Indonesia and the Philippines - Juoro, Umar (1989)
The paper chiefly measures agglomeration economies in both the production and consumption sectors in Indonesia and the Philippines. It's empirical model estimates the returns to scale parameter which represents localization economies for three-digit manufacturing, and urbanization economies for the entire consumer service sector. Regression results confirm the role of agglomeration economies in explaining the concentration of producers and consumers in the large urban areas. Agglomeration economies for the manufacturing sector are seen to arise from localization economies and those for the consumer service sector, from urbanization economies. The paper also features briefly a survey of literature on agglomeration economies, an assessment of industrial and consumer service distribution in the two countries, and policy recommendations.
Keywords: Philippines -- Literary collections; Indonesia -- Literary collections